2004
DOI: 10.1038/sj.emboj.7600246
|View full text |Cite
|
Sign up to set email alerts
|

A second human antiretroviral factor, APOBEC3F, is suppressed by the HIV-1 and HIV-2 Vif proteins

Abstract: The HIV‐1 Vif protein suppresses the inhibition of viral replication caused by the human antiretroviral factor APOBEC3G. As a result, HIV‐1 mutants that do not express the Vif protein are replication incompetent in ‘nonpermissive’ cells, such as primary T cells and the T‐cell line CEM, that express APOBEC3G. In contrast, Vif‐defective HIV‐1 replicates effectively in ‘permissive’ cell lines, such as a derivative of CEM termed CEM‐SS, that do not express APOBEC3G. Here, we show that a second human protein, APOBE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
514
3
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(552 citation statements)
references
References 33 publications
32
514
3
3
Order By: Relevance
“…However, hA3F and hA3G mRNA abundances revealed a positive, linear relationship (Pearson's correlation coefficient of 0.283; P ϭ 0.003) (Fig. 2), in agreement with previous studies in which hA3F and hA3G showed similar patterns of expression in tissues and were postulated to be coordinately regulated (1,12,26). It should be noted that our cross-sectional survey was not aimed at identifying long-term nonprogressors and, therefore, did not include sufficient numbers to allow valid statistical evaluations of this subgroup.…”
supporting
confidence: 91%
“…However, hA3F and hA3G mRNA abundances revealed a positive, linear relationship (Pearson's correlation coefficient of 0.283; P ϭ 0.003) (Fig. 2), in agreement with previous studies in which hA3F and hA3G showed similar patterns of expression in tissues and were postulated to be coordinately regulated (1,12,26). It should be noted that our cross-sectional survey was not aimed at identifying long-term nonprogressors and, therefore, did not include sufficient numbers to allow valid statistical evaluations of this subgroup.…”
supporting
confidence: 91%
“…The initial report of the APO-BEC3 gene cluster failed to detect expression of A3G or A3B in human liver by Northern blotting; however, two subsequent studies demonstrated co-expression of A3G and A3F in many organs, including the human liver, by Northern blotting or RT-PCR. 20,42,43 Our study confirms the expression of A3G and A3F in normal human liver and proves the hepatic expression of A3B mRNA. Thus, the concluding statement of Rösler et al 33 that a role of APOBEC3 cytidine deaminases in the HBV life cycle is speculative because expression of cytidine deaminases in untransformed liver has not been shown has to be amended.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with this hypothesis, it was recently shown that nonfunctional human A3Z3 alleles are highly prevalent and have been actively selected for (24,62). The discovery of the cellular antiviral cytidine deaminase A3G in search for the Vif cofactor explained many in vitro observations regarding the replication of HIV-1 and HIV-1 ⌬vif in specific human cells (5,49,78,91,100). It also contributed to explain the narrow host range of HIV-1 that shows spreading replication only in humans and chimpanzees (49,59).…”
Section: Discussionmentioning
confidence: 56%